Metronomic chemotherapy offsets HIFα induction upon maximum‐tolerated dose in metastatic cancers. Issue 9 (20th July 2020) - Schito, Luana; Rey, Sergio; Xu, Ping; Man, Shan; Cruz‐Muñoz, William; Kerbel, Robert S
Abstract: Conventional maximum‐tolerated dose (MTD) chemotherapy relies on periodic, massive cancer cell ablation events followed by treatment‐free intermissions, stereotypically resulting in resistance, relapse, and mortality. Furthermore, MTD chemotherapy can promote metastatic dissemination via activation of a transcriptional program dependent on hypoxia‐inducible factor (HIF)‐1α and (HIF)‐2α (hereafter referred to as HIFα). Instead, frequent low‐dose metronomic (LDM) chemotherapy displays less adverse effects while preserving significant pre‐clinical anticancer activity. Consequently, we hereby compared the effect of MTD or LDM chemotherapy upon HIFα in models of advanced, metastatic colon and breast cancer. Our results revealed that LDM chemotherapy could offset paralog‐specific, MTD‐dependent HIFα induction in colon cancers disseminating to the liver and lungs, while limiting HIFα and hypoxia in breast cancer lung metastases. Moreover, we assessed the translational significance of HIFα activity in colorectal and breast TCGA/microarray data, by developing two compact, 11‐gene transcriptomic signatures allowing the stratification/identification of patients likely to benefit from LDM and/or HIFα‐targeting therapies. Altogether, these results suggest LDM chemotherapy as a potential maintenance strategy to stave off HIFα induction within the intra‐metastatic tumor microenvironment. Synopsis: Low‐dose metronomic (LDM) chemotherapy offsets intra‐metastatic tumoral hypoxia, hypoxia‐inducible factor (HIF)‐α induction, and angiogenic responses elicited by conventional maximum‐tolerated dose (MTD) therapies in models of advanced, metastatic colon and breast cancer. LDM chemotherapy offsets HIF‐1α induction caused by MTD chemotherapy in large liver and lung metastases from colon and breast cancers, respectively; this effect is counterbalanced by HIF‐2α in colon cancer. HIF‐1α and ‐2α induction caused by MTD chemotherapy regimens is independent of metastatic tumor size. LDM chemotherapy decreases intra‐metastatic tumor hypoxic fractions, whilst leaving lung parenchymal perfusion unaffected. Intra‐metastatic tumor hypoxia parallels both microvessel density and HIFα expression. HIFα paralog expression depends on metastatic size and microenvironmental factors within the target organ. Abstract : Low‐dose metronomic (LDM) chemotherapy offsets intra‐metastatic tumoral hypoxia, hypoxia‐inducible factor (HIF)‐α induction, and angiogenic responses elicited by conventional maximum‐tolerated dose (MTD) therapies in models of advanced, metastatic colon and breast cancer.